Therapeutic potential of flavonoids and rutin against inflammation-induced on a huntington animal model - David Calderón Guzmán; Norma Osnaya Brizuela; Maribel Ortiz Herrera; Hugo Juárez Olguín; Armando Valenzuela Peraza; Alberto Rojas Ochoa; Ernestina Hernández García; Rafael Coria Jiménez; Daniel Santamaria del Angel (PLoS ONE, 2026)
This study tested the hypothesis that flavonoids (diosmine, hesperidin and rutin®) play a protective role in the brain and duodenum against 3-Nitropropionic acid (3-NPA) free radical induced inflammation. This was achieved by measuring the levels of GABA, 5-HIAA, dopamine and some inflammation and oxidative stress markers. Male young Wistar rats (weight 60g) received Salmonella thyphimurium ATCC14028 1x10 6 CFU/g every week, for two consecutive weeks, plus the following treatments: group A, 0.9% NaCl (Control); group B, diosmine (300 mg) + hesperidin (33.3g) + rutin (150 mg/kg); group C, 3-NPA; group D, 3-NPA + mix of flavonoids with 1 ml of rutin® per rat. 3-NPA administration was at 24 mg/kgW by intraperitoneal route and the flavonoids were orally administered at every 48 hours for 15 days. At the moment of euthanasia, the blood was obtained to assess Interleukine-6, glucose, triglycerides and hemoglobin levels. Brain and duodenum were obtained to measure GABA, dopamine, 5-HIAA, lipoperoxidation, reduced glutathione (GSH), total ATPase concentrations and catalase activity using validated methods. The brains, stomach and duodenum were dissected for histological analysis. In group A, there is a decrease in interleukine-6 levels (p = 0.009). In the cortex region of animals in group C, dopamine experienced a significant decrease (p = 0.012). GABA increased (p = 0.001) in cerebellum regions of animals in the groups A, B and C. ATPase activity increased (p = 0.013) in cerebellum regions in animals of groups C and D. Lipoperoxidation diminished (p = 0.043) in cerebellum region of group D. Catalase activity diminished (p = 0.043) in Cortex region of animals in groups B and D, and (p = 0.002) in cerebellum region of animals in groups A and B. Besides, histological changes revealed marked lesions of neuronal cells in experimental animals treated with nitro propionic acid. The protective role of flavonoids and rutin compounds on inhibition of the inflammatory response and correction of the fundamental oxidant/antioxidant imbalance in animals suffering from Huntington diseases are important vistas for further research.